Pengembangan Media Video Mengajar dengan Menerapkan Model Pembelajaran Case Method dan Team-Based Project untuk Perguruan Tinggi - Arnidah Arnidah; Citra Rosalyn Anwar; Dedy Aswan (Peneliti.net, 2023)
The classroom learning model's criteria must use one or a combination of case-solving learning methods (case method or project-based group learning (team-based project). Based on the Higher Education Key Performance Indicator (IKU) number seven, an application example is needed to avoid causing many perceptions. This research is expected to answer lecturers' needs for examples of the application of team-based projects and case methods. The objectives are: 1) analyze the needs of teaching video media by applying team-based project learning models and case methods, 2) design teaching video media by applying team-based project learning models and case methods, 3) Find out the level of validity and practicality of teaching video media by applying team-based project learning models and case methods. This research uses Thiagarajan 4D model development research with 4D stages adapted into 3D through the define, design, development stages. This research was conducted in the Educational Technology Study Program FIP UNM, the research subjects of seven lecturer. Data collection used interview guidelines, needs identification questionnaires, media expert validation questionnaires, content/material experts, and trial questionnaires. Data analysis methods consist of qualitative descriptive analysis and descriptive statistical analysis. The results showed that: 1) the development of teaching videos by applying the case-solving learning model (case method or project-based group learning (team-based project) is in the category of very needed. 2) product design based on content / material validation in the very good category, media validation in the very good category, trial results are in the very good category. The classroom learning model's criteria must use one or a combination of case-solving learning methods (case method or project-based group learning (team-based project). Based on the Higher Education Key Performance Indicator (IKU) number seven, an application example is needed to avoid causing many perceptions. This research is expected to answer lecturers' needs for examples of the application of team-based projects and case methods. The objectives are: 1) analyze the needs of teaching video media by applying team-based project learning models and case methods, 2) design teaching video media by applying team-based project learning models and case methods, 3) Find out the level of validity and practicality of teaching video media by applying team-based project learning models and case methods. This research uses Thiagarajan 4D model development research with 4D stages adapted into 3D through the define, design, development stages. This research was conducted in the Educational Technology Study Program FIP UNM, the research subjects of seven lecturer. Data collection used interview guidelines, needs identification questionnaires, media expert validation questionnaires, content/material experts, and trial questionnaires. Data analysis methods consist of qualitative descriptive analysis and descriptive statistical analysis. The results showed that: 1) the development of teaching videos by applying the case-solving learning model (case method or project-based group learning (team-based project) is in the category of very needed. 2) product design based on content / material validation in the very good category, media validation in the very good category, trial results are in the very good category.